The Distribution of Phosphatidylcholine Species in Superficial-Type Pharyngeal Carcinoma. (8th March 2017) - Ishikawa, Seiji; Tateya, Ichiro; Hayasaka, Takahiro; Shinriki, Satoru; Masaki, Noritaka; Hirano, Shigeru; Kitamura, Morimasa; Muto, Manabu; Morita, Shuko; Setou, Mitsutoshi; Ito, Juichi
Abstract : Objectives . Superficial-type pharyngeal squamous cell carcinoma (STPSCC) is defined as carcinoma in situ or microinvasive squamous cell carcinoma without invasion to the muscular layer. An exploration of the biological characteristics of STPSCC could uncover the invasion mechanism of this carcinoma. Phosphatidylcholine (PC) in combination with fatty acids is considered to play an important role in cell motility. Imaging mass spectrometry (IMS) is especially suitable for phospholipid analysis because this technique can distinguish even fatty acid compositions. Study Design . IMS analysis of frozen human specimens. Methods . IMS analysis was conducted to elucidate the distribution of PC species in STPSCC tissues. STPSCC tissue sections from five patients were analyzed, and we identified the signals that showed significant increases in the subepithelial invasive region relative to the superficial region. Results . Three kinds of PC species containing arachidonic acid, that is, PC (16:0/20:4), PC (18:1/20:4), and PC (18:0/20:4), were increased in the subepithelial invasive region. Conclusion . These results may be associated with the invasion mechanism of hypopharyngeal carcinoma.